The Effect of E-Wallet Use and Financial Literacy on Generation Z's Consumptive Behavior with Self-Control as a Moderation Variable - Rosyanti, Amrina; Santoso, Fahrul Imam (Journal of Economics and Social Sciences (JESS), 2026)
This study aims to analyze the influence of e-wallet usage and financial literacy on the consumptive behavior of Generation Z in Yogyakarta with self-control as a moderating variable. This study uses a quantitative method with the selected sampling technique, namely the purposive sampling method. The sample used in the study amounted to 126 Gen Z or respondents obtained through questionnaire distribution and data processed using the SEM-PLS model. The results show that e-wallet usage and financial literacy do not significantly influence consumptive behavior. In addition, self-control also does not significantly moderate the relationship between e-wallet usage and financial literacy on consumptive behavior of Generation Z in Yogyakarta. However, in contrast, self-control has a negative and significant effect on consumptive behavior of Generation Z in Yogyakarta. This means that there is still good control from Gen Z Yogyakarta in regulating and suppressing consumptive behavior for their daily lives. Based on this study, it shows that financial understanding and the use of technology are not always factors in consumptive behavior.